2018
DOI: 10.1088/1361-648x/aacedb
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale study of stacking faults in Zr hydrides and implications on hydride formation

Abstract: We performed atomic-scale ab initio calculations to investigate the stacking fault (SF) properties of the metastable ζ-ZrH zirconium hydride. The effect of H near the SF was found to entail the existence of negative SF energies, showing that the ζ compound is probably unstable with respect to shearing in the basal plane. The effect of temperature on SFs was investigated by means of free energy calculations in the quasiharmonic approximation. This evidenced unexpectedly large temperature effects, confirming the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Since the lattice parameter that minimizes the free energy of the system depends on temperature (thermal expansion), it would be necessary, in order to refine the thermodynamic description of the system at zero pressure, to calculate phonon frequencies for different lattice parameters and take those values that minimize the vibration free energy, which constitutes the quasiharmonic approximation. However, this kind of study has shown [44] that even at relatively elevated temperature (800 K) the free energy difference between the harmonic (adopted in this work and that consists in calculating F vib at fixed volume) and quasiharmonic approximation is only a few meV/atom, a degree of refinement of second 7 order with respect to other uncertainties in the ab initio input data. We therefore opted to work at constant lattice parameter (the 0 K equilibrium value) to preserve computational resources.…”
Section: Ii-3 Methodology For Phonons and Magnonsmentioning
confidence: 95%
“…Since the lattice parameter that minimizes the free energy of the system depends on temperature (thermal expansion), it would be necessary, in order to refine the thermodynamic description of the system at zero pressure, to calculate phonon frequencies for different lattice parameters and take those values that minimize the vibration free energy, which constitutes the quasiharmonic approximation. However, this kind of study has shown [44] that even at relatively elevated temperature (800 K) the free energy difference between the harmonic (adopted in this work and that consists in calculating F vib at fixed volume) and quasiharmonic approximation is only a few meV/atom, a degree of refinement of second 7 order with respect to other uncertainties in the ab initio input data. We therefore opted to work at constant lattice parameter (the 0 K equilibrium value) to preserve computational resources.…”
Section: Ii-3 Methodology For Phonons and Magnonsmentioning
confidence: 95%